Happy Entrepreneurs? Everywhere? A Meta-Analysis of Entrepreneurship and Wellbeing. (March 2023) - Stephan, Ute; Rauch, Andreas; Hatak, Isabella
Entrepreneurship can be fulfilling and enhance wellbeing, but also highly stressful and diminish wellbeing. This meta-analytical review synthesizes 319 effect sizes from 94 studies and 82 countries to establish whether individuals derive greater wellbeing from working for themselves or for someone else. The answer is partly positive in favor of entrepreneurship but depends on the components of wellbeing under investigation (positive wellbeing or negative wellbeing/mental illbeing) and the institutional context (especially the rule of law). We contribute by developing the component view of wellbeing as an organizing framework and by advancing an institutional perspective to guide research on entrepreneurs' wellbeing.